Hydrogen production enhancement from low-temperature catalytic thermochemical processing of palm oil empty fruit bunches / Khairul Ashraf Kamarudin - Kamarudin, Khairul Ashraf (2018)
A low-temperature thermo-chemical conversion of biomass to maximise the hydrogen-rich sync gas product to replicate a one-step hydrogen production using palm oil empty fruit bunches (EFB) pellets as an alternative process for renewable hydrogen production was studied. Catalysts CaO and NaOH were selected due to its availability and low price. The yields and distributions of the gas products were studied under various operating conditions. The thermochemical characterization was completed which include proximate, ultimate and thermogravimetry analysis in determining the need for pre-treatment as well as the design of suitable thermal conversion process